OVERVIEW OF HEALTH INFORMATION MANAGEMENT EMERGENCY AND IMPLEMENTATION OF SISRUTE AT dr. H. MOCH. ANSARI SALEH BANJARMASIN GENERAL HOSPITAL - RARA, RABIATUL ADAWIAH; Nurbaiti, Nurbaiti; Heriyadi, Muhammad; Nurhadijah, Nurhadijah (Politeknik Unggulan Kalimantan, 2025)
RSUD dr. H. Moch. Ansari Saleh Banjarmasin, the number of patient referrals received through SISRUTE at Unit 119 has been operational since August 1, 2024, as part of strengthening digital-based emergency services. The utilization of SISRUTE, which is integrated with the Electronic Medical Record (ERM) system, supports the rapid and accurate exchange of clinical patient information. Based on data from August 1, 2024, to the end of December 2025, a total of 459 patients were referred through SISRUTE, where the referral data was documented in the ERM and used as a basis for the continuity of medical services at the receiving healthcare facility. These data indicate that the utilization of SISRUTE plays a vital role in supporting the smooth process of emergency patient referrals and enhancing coordination and service efficiency between healthcare facilities. This study is a qualitative research. Qualitative research in this study was used to identify the factors behind the return of medical record files based on the 5M framework (Man, Machine, Method, Material, and Money). According to Sugiyono (2018), qualitative research methods are used to examine natural object conditions, where the researcher serves as the key instrument, data collection techniques are carried out through triangulation (combined), data analysis is inductive, and the results emphasize meaning rather than generalization. The results of this study indicate that the Integrated Referral Information System (SISRUTE) has been implemented. SISRUTE is an information technology and internet-based health referral information system application designed to integrate and simplify the patient referral process between healthcare facilities, from primary levels (e.g., community health centers/clinics) to vertical hospitals or higher healthcare facilities online. The objective is to ensure that referrals are carried out quickly, accurately, effectively, and efficiently according to the patient's medical needs and the competence of the destination facility.